Current status of the pyrolysis and gasification mechanism of biomass; Energies; Vol. 14, iss. 22 - Glushkov D. O. Dmitry Olegovich; Nyashina G. S. Galina Sergeevna; Shvets A. S. Anatoly Sergeevich; Pereira A. Amaro; Ramanathan A. Anand (2021, 2021)
Title screen